Contraception Use Among Reproductive‐Age Women With Rheumatic Diseases. Issue 8 (3rd July 2019) - Birru Talabi, Mehret; Clowse, Megan E. B.; Blalock, Susan J.; Moreland, Larry; Siripong, Nalyn; Borrero, Sonya
Abstract : Objective: To determine contraception use among a cohort of reproductive‐age women (ages 18–50 years) with rheumatic diseases. Methods: We conducted a study of administrative data from a single, large medical center between the years 2013 and 2014. Women who had 1 of 21 possible rheumatic disease diagnoses and had at least 2 outpatient rheumatology visits were included in this analysis. We used logistic regression analyses to evaluate adjusted associations between the use of prescription contraception, use of potentially fetotoxic medications, and visits with rheumatologists, primary care providers, and gynecologists. Results: Of 2, 455 women in this sample, 32.1% received any prescription contraception, and 7.9% of women used highly effective prescription methods (intrauterine devices, implants, and surgical sterilization). More than 70% of women took ≥1 type of fetotoxic medication during the 2‐year study timeframe. Fetotoxic medication use was not associated with overall use of prescription contraception, but was associated with the use of highly effective contraceptive methods (adjusted odds ratio [OR] 2.26 [95% confidence interval (95% CI) 1.44–3.54]). Women who saw gynecologists or primary care providers were more likely to use prescription contraception overall (adjusted OR 3.35 [95% CI 2.77–4.05] and 1.43 [95% CI 1.18–1.73], respectively). Women who saw gynecologists were more likely to use highly versus moderately effective contraceptive methods (adjusted OR 2.35 [95% CI 1.41–3.94]). Rheumatology visits were not associated with use of prescription contraception in any models. Conclusion: This is the largest study to date to describe contraceptive use among reproductive‐age women with rheumatic diseases, and the findings reveal low use of prescription contraception. Urgent efforts are needed to improve contraceptive care and access for some women with rheumatic diseases.